Performance of adaptive MIMO switching for cognitive MC-CDMA system - Leela, S.; Vishvaksenan, Kuttathati Srinivasan (Cluster computing, 2019)
The future 5G wireless network will be identified by flexibility design, high combination of services, and higher data rate. In this treatise, we present the performance evaluation physical layer design for multi-carrier code-division-multiple-access (MC-CDMA) system for cognitive radio network (CRN) employing link adaptive multiple-input multiple- output (MIMO). CRN in conjunction with MIMO promises to achieve massive amelioration in system bandwidth. We consider link adaption scheme (LAS) which will select modulation scheme and MIMO profile based on channel parameters. CRN is a device in wireless communication which can sense the idle unused spectrum and allocate the spectrum dynamically to base station. We utilize sub-band frequency of CRN for multi-carrier communication and to extract for user-specific spreader in CDMA system. Further, we realize iterative decoder at the receiver to achieve better error-rate performance for CRN based MIMO MC-CDMA system with less signal-to-noise ratio (SNR). Furthermore,We study the performance of adaptive MIMO scheme with CRN defined MC-CDMA for Stanford University Interim channel model specifications. We discern through computer simulations that CRN based MC-CDMA system with adaptive MIMO scheme achieves significant performance enhancement both in error-rate and data rate.